Synthetic Biology: Designing Novel Organisms for Biotechnological Applications - Fadel, Hameed Hakim Mohi; Hasson, Murtatha Taha Nasser (American Journal of Botany and Bioengineering, 2024)
Synthetic biology is an emerging field that aims to design and genetically engineer novel organisms and biological systems for biotechnological applications. Rapid advancements in the field may yield disruptions in several industries, all the way from sugar and crude oil production to drug discovery and biomedicine. Synthesis of novel bioactive natural products may become cheaper than isolation from native sources, while bioremediation may revolutionize the oil, metal, and plastics industry. Synthetic biology encompasses several innovative engineering concepts for rationally designing biological systems, which are mathematically predictable. The design scope ranges from small, engineered proteins to large, transgenic organisms, or even assemblies of such organisms. At this moment, the full scope of possibilities is largely unexplored. It is thereby imperative for natural scientists to investigate and understand the myriad of possible implications of this rapidly expanding field—both in terms of basic science and public concerns. One of the main applications of synthetic biology is the transformation of microorganisms into green factories for the high-yield production of biofuels, pharmaceutical precursors, non-protein amino acids, and industrially challenging enzymes. Owing to the various applications, the field is heavily funded, with investment figures in the billions of US dollars. Although a rapidly advancing field, there are major challenges in synthetic biology, such as the difficulty in inserting large engineered pathways into genomes while accomplishing near-native expression and without disturbing the host’s native metabolism. However, the effects of design interventions are starting to gain predictive power, setting the stage for improved genetic circuitry. In order to maximize potential social benefit and minimize the drawbacks, it is important that ethical considerations keep pace with developments.